Arrhythmogenicity of Various Anesthesia Techniques During Abdominal Cancer Surgery - M. M Shemetova; V. E. Khoronenko; A. A. Aleksin (Общая реаниматология)
Objective: to develop an algorithm in order to choose a method for anesthesia and its components that minimally affect heart rhythm and the cardiac conduction system (CCS) for patients at high risk for perioperative arrhythmias. Subjects and methods. Seventy-five patients aged 62.2±9.63 years, who received cardiotropic therapy for the compensation of cardiovascular diseases and had undergone surgery for abdominal malignancies, were examined. According to the anesthesia technique, the patients were randomized into 4 groups: 1) (n=16) multimodal intravenous general analgesia (IGA); 2) (n=17) sevoflurane inhalation anesthesia (IA); 3) (n=19) combination epidural anesthesia (EA) and IGA; 4) (n=20) a combination of EA and IA. The effects of anesthesia components on heart rhythm and CCS were evaluated from the results of Holter continuous ECG monitoring. Results. A change in the heart rhythm pattern was recorded in all the study group patients. Group 1 had increased ectopic activity: a rise in the number of supraventricular and ventricular premature beats (SPB and VPB) by 67.2 and 29.9%, respectively (p<0.05), which required correction in 4 of the 16 patients. The other groups showed a reverse tendency: a decrease in the number of SPB and VPB (by 10.3 and 9.37% in Group 2, by 53.6 and 29.5% in Group 3, and by 49.3 and 37.8% in Group 4, respectively), and the development of cardiac impulse conduction disturbances (pauses, > 2000 msec), which required special correction in 8 of the 19 patients in Group 3 and in 5 of the 20 patients in Group 4, respectively. There were no postoperative complications associated with cardiac rhythm or conduction disturbances. Conclusion. The choice of an anesthesia technique at high risk for perioperative arrhythmias is determined by the baseline cardiological status of a patient and by the nature of the arrhythmogenic effect of anesthetics. Multimodal IGA is preferred for baseline conduction disturbances. Sympathetic epidural blocks in combination with IGA and IA are indicated for patients with tachysystoles. Sevoflurane has no considerable effect on rhythm and CCS. Key words: peri-operative arrhythmias, anesthesia for high vascular risk patients, operation, cardiotropic therapy.